Mining and the Quality of Public Services : The Role of Local Governance and Decentralization - Konte, Maty; Vincent, Rose Camille (World Bank, Washington, DC, 2020)
This paper investigates the local effects of mining on the quality of public services and on people's optimism about their future living conditions. It also assesses the mediating role of local institutions and local governments~^!!^ taxing rights in shaping the proximity-to-mine effects. The empirical framework connects more than 130,000 respondents from the Afrobarometer survey data (2005-2015) to their closest mines based on the geolocation coordinates of the enumeration areas (EA) and data on the mines and their respective status from the SNL Metals & Mining. The geo-referenced data are matched with new indicators on local governments~^!!^ taxing rights across the African continent. The results suggest that citizens living near an active mine are less likely to approve government performance in key public goods and services -- including health, job creation and improving living standards of the poor. On the mediating role of local governance and local taxing rights, the findings point to a negative effect of local corruption, yet a positive effect of local authorities’ discretion over tax and revenues. However, the positive marginal effect of local taxing powers tends to reduce in environments with poor quality of local governance, high incidence of bribe payment and low level of trust in local government officials. Residents of mining communities with low corruption and comparatively high-level of raising revenue ability have the highest rate of positive appraisal compared to the other scenarios.